Strategies for remote enantiocontrol in chiral gold(iii) complexes applied to catalytic enantioselective γ, δ-Diels–Alder reactions. Issue 25 (19th March 2020) - Reid, Jolene P.; Hu, Mingyou; Ito, Susumu; Huang, Banruo; Hong, Cynthia M.; Xiang, Hengye; Sigman, Matthew S.; Toste, F. Dean
Abstract : Chiral square planar gold(iii ) complexes are employed as catalysts in asymmetric Diels–Alder reactions. The non-covalent interactions responsible for the enantioselectivity are revealed through multivariate linear regression analysis. Abstract : The use of chiral square planar gold(iii ) complexes to access enantioenriched products has rarely been applied in asymmetric catalysis. In this context, we report a mechanistic and synthetic investigation into the use of N-heterocyclic (NHC) gold(iii ) complexes in γ, δ-Diels–Alder reactions of 2, 4-dienals with cyclopentadiene. The optimal catalyst bearing a unique 2-chloro-1-naphthyl substituent allowed efficient synthesis of functionally rich carbocycles in good yields, diastereo- and enantioselectivities. Transition state and multivariate linear regression (MLR) analysis of both catalyst and substrate trends using molecular descriptors derived from designer parameter acquisition platforms, reveals attractive non-covalent interactions (NCIs) to be key selectivity determinates. These analyses demonstrate that a putative π–π interaction between the substrate proximal double bond and the catalyst aromatic group is an essential feature for high enantioselectivity.